2019
DOI: 10.1002/anie.201910450
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyampholyte Janus‐like Microgels by Coacervation of Reactive Precursors in Precipitation Polymerization

Abstract: Controlling the distribution of ionizable groups of opposite charge in microgels is an extremely challenging task, which could open new pathways to design a new generation of stimuli‐responsive colloids. Herein, we report a straightforward approach for the synthesis of polyampholyte Janus‐like microgels, where ionizable groups of opposite charge are located on different sides of the colloidal network. This synthesis approach is based on the controlled self‐assembly of growing polyelectrolyte microgel precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…A 3D cross-linked polymer colloids, nanogels (NGs) as nanocarriers have attracted much attention in biomedical applications, including drug/enzyme delivery, images and therapy of tumors, due to their unique properties [ [14] , [15] , [16] ]. All the time we explored various NGs that having the controllable size, deformable softness, highly porous network, excellent biocompatibility and stimuli-responsiveness can be employed as functional nanocarriers for improved tumor theranostics [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. In particular, the biocompatible PVCL-based NGs exist a volume phase transition temperature (VPTT) of about 35 °C which is close to body temperature, and high cargo loading capacity along with enhanced tumor accumulation for biomedical purposes [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D cross-linked polymer colloids, nanogels (NGs) as nanocarriers have attracted much attention in biomedical applications, including drug/enzyme delivery, images and therapy of tumors, due to their unique properties [ [14] , [15] , [16] ]. All the time we explored various NGs that having the controllable size, deformable softness, highly porous network, excellent biocompatibility and stimuli-responsiveness can be employed as functional nanocarriers for improved tumor theranostics [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. In particular, the biocompatible PVCL-based NGs exist a volume phase transition temperature (VPTT) of about 35 °C which is close to body temperature, and high cargo loading capacity along with enhanced tumor accumulation for biomedical purposes [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…[30] Recent progress in synthesis enabled preparation nanogels with internal compartments and various shapes. [31][32][33][34][35] Furthermore,i sw as observed that the extreme softness of ultra-low cross-linked (ULC) nanogels leads to unique properties. [36] ULC nanogels exhibit high swellability and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Complex coacervates were recognized to resemble these membraneless organelles and serve as cell model systems 94 , 95 and were proposed as protocells for the origin of life. 96 , 97 Since then, many interesting studies showed coacervates dynamic assembly and disassembly upon different stimuli 98 , 99 and their assembly into more complex, multiphase systems. 98 , 100 , 101 However, using complex coacervates, a polymer-rich phase is generated, as well as a polymer-poor phase.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“… 96 , 97 Since then, many interesting studies showed coacervates dynamic assembly and disassembly upon different stimuli 98 , 99 and their assembly into more complex, multiphase systems. 98 , 100 , 101 However, using complex coacervates, a polymer-rich phase is generated, as well as a polymer-poor phase. This is not an accurate representation of the cell.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%